Good Governance and Standards of Compliance with Public Services in Indonesia: A Study on the Province Government - Ikin Solikin, Dityo Adinugraha and Amir Machmud (International Journal of Advanced Science and Technology, 2020)
This study aims to analyze aims to analyze the effect of the effect of implementing good governance on the level of compliance with public service standards. The study was conducted in 31 provinces in Indonesia. The study method uses the survey The assessment of good governance is divided into four arenas, arenas of political officials, arenas of bureaucracy, arenas of civil society, and arenas of economic society. In this study used multiple linear regression analysis techniques. The results of the study indicate that the arena of political officials in good governance does not affect the level of compliance with public service standards. While both the bureaucratic arena in good governance, the arena of civil society in good governance, and the arena of economic society in good governance have an influence on the level of compliance with public service standards. This finding implies that to increase the level of compliance with public service standards the role of various arenas in good governance, especially the arena of bureaucracy, the arena of civil society and the arena of economic society.